Foundations Of Increasing The Activity Of Women And Girls In Physical Education And Sports (Journal of Pedagogical Inventions and Practices, 2024)
The article describes the concept of education development has been developed, its main task is to form a deep loyalty to the material and spiritual values of the people in the younger generation, to learn and to introduce the lost elements of traditional culture. In the article, problem of maintaining and strengthening physical and mental health, increasing physical activity, and women's longevity have been described. The researchers’ point of view and works on the problem have been analyzed in the paper